Prevalence and association of non-alcoholic fatty liver disease and insulin resistance among non-diabetic obese, overweight, and metabolically obese normal-weight adult patients attending at a tertiary care hospital in Eastern India - Samik Pramanik; Jimmy Barua; Lokanathan V; Sharmistha Roy (Asian Journal of Medical Sciences)
Background: Worldwide, the incidence of obesity, overweight, and metabolic syndrome is dramatically increasing. Non-alcoholic fatty liver disease (NAFLD) is associated with both obesity/overweight and metabolic syndrome.